Predictors allowing early discharge after interventional treatment of acute coronary syndrome patients - Bauer, Dávid; Neuberg, Marek; Nováčková, Markéta; Mašek, Petr; Kočka, Viktor; Moťovská, Zuzana; Toušek, Petr (European heart journal supplements, 2022)
Many scoring systems for predicting the outcomes of patients with acute coronary syndrome (ACS) have been proposed. In some populations, a significant reduction in length of hospital stay may be achieved without compromising patient prognoses. However, the use of such scoring systems in clinical practice is limited. The aim of this study was to propose a universal list of predictors that can identify low-risk ACS patients who may be eligible for an earlier hospital discharge without increased short-term risk for major adverse cardiac events. A cohort of 1420 patients diagnosed with ACS were enrolled into a single-centre registry between October 2018 and December 2020. Clinical, laboratory, echocardiographic, and angiographic measurements were taken for each patient and entered into the study database. Using retrospective univariant analyses of patients treated with percutaneous coronary intervention (PCI) (n = 932), we compared each predictor to 30-day mortality rate using the Czech national registry of dead people. Eleven predictors correlate significantly with 30-day survival: age <80 years, ejection fraction >50%, no cardiopulmonary resuscitation, no mechanical ventilation needed, Killip class I at admission, haemoglobin levels >110 g/L while hospitalized, successful PCI procedure(s), no residual stenosis over 90%, Thrombolysis in Myocardial Infarction 3 flow after PCI, no left main stem disease, and no triple-vessel coronary artery disease. In all, presence of all predictors applies to 328 patients (35.2% of the cohort), who maintained a 100% survival rate at 30 days. A combination of clinical, echocardiographic, and angiographic findings provides valuable information for predicting the outcomes of patients with all types of ACS. We created a simple, useful tool for selecting low-risk patients eligible for early discharge.
Keywords: Acute coronary syndrome; Prognosis; Early discharge; Predictors; Low risk